Lead-Lag Relationship between Spot and Futures Price of the Nikkei Stock Average - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1995)
A study examines the lead-lag relationship between the spot index and futures price of the Nikkei Stock Average. Using daily data in the post-crash period, the interaction between the spot and futures series through the error correction model is investigated. Two versions of error correction models are considered, depending on the postulated long-run equilibrium relationship. It is found that lagged changes in the futures price affect the short-term adjustment in the spot index, but not vice versa. Forecasting models for the spot index are also constructed using the univariate time series approach and the vector autoregressive method. For the post-sample forecast comparison the error correction models produce the best results. The vector autoregressive method performs better than the martingale model, while the univariate time series method gives the poorest forecasts.